Polyethyleneimine mediated DNA transfection in schistosome parasites and regulation of the WNT signaling pathway by a dominant-negative SmMef2. - Shuang Liang; Matty Knight; Emmitt R Jolly (PLoS Neglected Tropical Diseases)
Schistosomiasis is a serious global problem and the second most devastating parasitic disease following malaria. Parasitic worms of the genus Schistosoma are the causative agents of schistosomiasis and infect more than 240 million people worldwide. The paucity of molecular tools to manipulate schistosome gene expression has made an understanding of genetic pathways in these parasites difficult, increasing the challenge of identifying new potential drugs for treatment. Here, we describe the use of a formulation of polyethyleneimine (PEI) as an alternative to electroporation for the efficacious transfection of genetic material into schistosome parasites. We show efficient expression of genes from a heterologous CMV promoter and from the schistosome Sm23 promoter. Using the schistosome myocyte enhancer factor 2 (SmMef2), a transcriptional activator critical for myogenesis and other developmental pathways, we describe the development of a dominant-negative form of the schistosome Mef2. Using this mutant, we provide evidence that SmMef2 may regulate genes in the WNT pathway. We also show that SmMef2 regulates its own expression levels. These data demonstrate the use of PEI to facilitate effective transfection of nucleic acids into schistosomes, aiding in the study of schistosome gene expression and regulation, and development of genetic tools for the characterization of molecular pathways in these parasites.